(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This paper discloses the activity of mosques in Tashkent in the second half of the nineteenth century. The author studies the role of mosques in the social life of the city, the influence of Russian colonial policy on religious institutions, and the economy of the mosques. In addition, the article illustrates the staff of the mosques and their incomes. The functions of mosques, apart from being prayer houses, are also examined. Archival documents and the works of scholars of the studied period have formed the foundation of the article.